Cover Feature: Combining Photodeprotection and Ligation into a Dual‐Color Gated Reaction System (Chem. Eur. J. 71/2020). Issue 71 (19th October 2020) - Alves, Jessica; Krappitz, Tim; Feist, Florian; Blinco, James P.; Barner‐Kowollik, Christopher
Abstract : Key wavelengths controlling a dual‐gated one‐pot reaction are paramount for the development of novel printing techniques. The visible‐light gate activates the photocatalyzed deprotection of a dithioacetal leading to a o‐methylbenzaldehyde. Upon the opening of the UV light gate, the o‐methylbenzaldehyde undergoes a light‐mediated Diels–Alder reaction with a dienophile. This dual‐gated system represents a step closer to two‐color wavelength‐activated photoresists. More information can be found in the Communication by J. P. Blinco, C. Barner‐Kowollik, et al. on page 16985 .